2007
DOI: 10.1093/bioinformatics/btm413
|View full text |Cite
|
Sign up to set email alerts
|

Sliding MinPD: building evolutionary networks of serial samples via an automated recombination detection approach

Abstract: Sliding MinPD combines distance-based phylogenetic methods with automated recombination detection based on the best-known sliding window approaches to reconstruct serial evolutionary networks. Its performance was evaluated through comprehensive simulation studies and was also applied to a set of serially-sampled HIV sequences from a single patient. The resulting network organizations reveal unique patterns of viral evolution and may help explain the emergence of disease-associated mutants and drug-resistant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Methods designed specifically for longitudinal datasets (e.g. Buendia and Narasimhan, 2007) could be used to confirm these recombinants. However, our analysis recovered far more recombinants within a single timepoint than the previous studies, which supports our overall conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods designed specifically for longitudinal datasets (e.g. Buendia and Narasimhan, 2007) could be used to confirm these recombinants. However, our analysis recovered far more recombinants within a single timepoint than the previous studies, which supports our overall conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that this method is not very powerful, especially when sequences are closely related (Posada and Crandall, 2001; Salminen, 2003). Improved bootscanning methods have been introduced that either do not require prior identification of parental sequences and incorporate distance measures as well (Martin et al, 2005) or that can incorporate serially sampled sequences into the analysis (Buendia and Narasimhan, 2007), both of which are more powerful methods than the original bootscanning implementation. An alternative approach is to use phylogenetic networks to investigate data sets that are suspected to contain recombinants (Huson and Bryant, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Despite much ongoing work in this area, there are currently no broadly applicable methods that can take as input multiple sequence alignments and give as output phylogenetic network graphs that explicitly depict recombination (called reticulate ⁄ recombination networks in Huson & Bryant 2006). However, some specialized applications exist, like SlidingMinPD (Buendia & Narasimhan 2007), which attempts to infer recombination networks for recombining viral sequences that have been serially sampled within an individual host.…”
Section: Dealing With Recombination In Molecular Evolution Studiesmentioning
confidence: 99%
“…Furthermore, these traditional phylogenetic methods assume that all the sequence data are from contemporaneous taxa, which is not valid for serially-sampled data from longitudinal studies. Several methods that estimate the phylogenetic relationship of serially-sampled data have been published since 2000 [ 1 , 9 - 14 ]. However, only one of these methods takes recombination into account: Sliding MinPD [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…
Background The HIV virus is known for its ability to exploit numerous genetic and evolutionary mechanisms to ensure its proliferation, among them, high replication, mutation and recombination rates. Sliding MinPD, a recently introduced computational method [ 1 ], was used to investigate the patterns of evolution of serially-sampled HIV-1 sequence data from eight patients with a special focus on the emergence of X4 strains. Unlike other phylogenetic methods, Sliding MinPD combines distance-based inference with a nonparametric bootstrap procedure and automated recombination detection to reconstruct the evolutionary history of longitudinal sequence data.
…”
mentioning
confidence: 99%